ANNOUNCED DEMOCRACY AND DENOUNCED OPPRESSION: A CASE OF RESISTANCE IN THE TEXTILE INDUSTRY OF MINAS GERAIS, BRAZIL - Saraiva, Luiz Alex Silva; Irigaray, Helio Arthur Reis (Revista de Negócios, 2011)
The democratization of company work places has been constantly emphasized, by those inside and outside of private organizations, as evidence of the evolution of such firms. At the same time, there is growing doubt about the real possibility of the status of the worker rising to that of citizen in the company environment. In order to discuss these aspects, this article is based on a qualitative research, which utilized documents and semi-structured interviews and was conducted in an industrial textile company in Minas Gerais. The reports denounce oppression in the firm, even though it is masked by the discourse of participation and organizational emancipation. The article concludes with reflections about resistance to this situation, which exists in spite of an unfavorable environment for the workers.